Identification of the Identical Human Mutation in ACVR1 in 2 Cats With Fibrodysplasia Ossificans Progressiva. Issue 4 (July 2019) - Casal, Margret L.; Engiles, Julie B.; Zakošek Pipan, Maja; Berkowitz, Asaf; Porat-Mosenco, Yael; Mai, Wilfried; Wurzburg, Kirsten; Xu, Mei-Qi; Allen, Robyn; ODonnell, Patricia A.; Henthorn, Paula S.; Thompson, Keith; et al.
Two domestic shorthair cats, 1 intact female and 1 intact male, presented with progressive limb lameness and digital deformities at 4 and 6 months of age. Stiffness and swelling of the distal thoracic and pelvic limb joints progressed to involve hip and shoulder joints, resulting in reduced mobility. Radiographs in both cats and computed tomography of the male cat revealed ankylosing, polyarticular deposits of extracortical heterotopic bone spanning multiple axial and appendicular joints, extending into adjacent musculotendinous tissues. All findings supported fibrodysplasia ossificans progressiva (FOP), a disorder characterized by toe malformations and progressive heterotopic ossification in humans. In both cats, molecular analyses revealed the same heterozygous mutation in the activin A receptor type I ( ACVR1 ) gene that occurs in humans with FOP. Several reports of heterotopic ossification in cats exist, but this is the first one to identify clinical FOP in 2 cats with the identical mutation that occurs in >95% of humans with FOP.